Elevated NGF provokes decidual lipid peroxidation and promotes preterm birth in mice - Yuhang Ge; Ruxin Teng; Zhaoyu Jia; Yongyue Li; Yafang Lu; Jia Yuan (Journal of Translational Medicine)
Abstract Background Preterm birth (PTB) is a major cause of neonatal morbidity and mortality worldwide, with infection and inflammation being the most common triggers. However, many cases of preterm labor have unknown causes. The maternal decidua is a highly dynamic and heterogeneous region, serving as the nexus at the maternal-fetal interface, connecting the mother and the fetus. Increasing evidence suggests that the maternal decidua plays a crucial role in the initiation of labor. Nerve growth factor (NGF), is an important member of the neurotrophin family and is identified to play a crucial role in initiating the decidual response. Methods To investigate whether NGF contributes to preterm birth via lipid peroxidation-dependent pathways, we selected both NGF and erastin (a pharmacological lipid peroxidation inducer) for parallel experimental treatments to examine how these pathways mediate the initiation of parturition. Mice were administered intraperitoneal injections of NGF and erastin. Gestational durations less than 19.5 days were classified as preterm birth. This study employed biological technologies and experimental methods to explore the initiation of delivery and the associated signaling pathways. Results Elevated NGF levels in late-stage pregnancy increased the incidence of preterm birth in mice, independent of decidual senescence, placenta abnormal structure and ovarian dysfunction. Instead, NGF treatment activated lipid peroxidation and upregulated inflammatory markers in maternal decidua, particularly cyclooxygenase enzymes, which are critical for labor initiation. Notably, administration of erastin corroborated these findings, leading to similar outcomes in preterm labor. Conclusions This study reveals the pivotal role of NGF signaling in promoting excessive lipid peroxidation to disrupt decidual homeostasis and ultimately triggering preterm labor in mice. Graphical Abstract